PROFESSIONAL FOREIGN LANGUAGE COURSE FOR INTERNATIONAL STUDENTS: APPROACHES TO CONTENT SELECTION (Филологический класс, 2019)
The research is devoted to a pedagogical problem that is topical for modern Russian higher education – the problem of content choice of professional foreign language training for foreign students. The purpose of the paper is to justify the approach to content selection of the discipline “Professional Foreign (Russian) Language” for foreign students who specialize in different areas of studies. The research is based on the application of general pedagogical theoretical and practical methods: analysis of pedagogical theory; experience of Russian and foreign pedagogy in professional language teaching; implementation of selected approaches and methodologies in practice; analysis of approbation. It is proposed to use the following methods in the learning process as a methodological basis for the formation of foreign professional competences such as a) teaching methods for communicative grammar and b) methods of genre-based pedagogy. The paper systematizes modern approaches to content selection for professional foreign language teaching. We propose the approach based on the universal educational material – general technical and humanitarian texts and lexical and grammatical constructions of various communicative directions. It is also proved that this approach allows to organize work in groups effectively. These groups consist of foreign students who studywithin different technical educational programs. The paper describes a systematic four-module system for professional Russian language teaching. This system is based on the complication of developing skills and abilities: from understanding of book speech through sentence transformation to their own speech (individual sentences in accordance with communicative tasks and whole texts relating to different genres of scientific speech). It is concluded that the implementation of the discipline „Professional Russian language“ based on the approach proposed in the paper for content selection and described methods ensures the development of all components of student professional foreign language competences. It also allows to organize the educational process in groups effectively. These groups consist of students who study within different technical educational programs.